Auditing the performance of the activities of the national poverty reduction strategy according to the program and policy manual prepared by the Federal Financial Supervision Bureau (Applied research in the Ministry of Labor and Social Affairs) - Amal Hameed Rasheed; Salim Awad Hadi; Baydaa Satar Lafta (Journal of Madenat Alelem University College, 2021)
The objective of the research is to explain the reality of the national strategy for poverty alleviation and define steps to conduct an audit of its performance in the researched ministry according to the Program and Policy Manual, and it represents the field of research in the Ministry of Labor and Social Affairs for the years (2010-2016) as the period of implementation of the national poverty reduction strategy (2010- 2014) Because of the delay in the allocation of its allocations, the strategy began to be implemented from (2012-2016), and the descriptive analytical approach has been adopted in the interpretation of this phenomenon. The research reached a set of conclusions, the most prominent of which was the failure of the national strategy to reduce poverty to achieve its goal of reducing poverty in Iraq by (30%) i.e. reducing the poverty rate from (23%) to (16%) at the end of its period. And the most prominent finding of the recommendations is to focus on the future of the accountability and accountability when activities are not implemented in the next strategies